Searching for a new biomarker for Alzheimer's disease based on BDNF receptor cleavage - Borlido, Carolina de Almeida (2020)
Tese de mestrado em Bioquímica (Bioquímica Médica), Universidade de Lisboa, Faculdade de Ciências, 2020